Ebers – Moll model :→ Figure should Ebers – Moll model for p–n-p transistor.

It involves two ideal diodes placed back to back with satuation current - IEo and – Ico and two dependent current – controlled current sources shunting the ideal diodes.

Currents and Voltages used in the Ebers-Moll equations

→ Let us see the equations of Ic and IE from Ebers – moll model. Applying KCL to the collector node, we get αN IE + IC = I IC = I – αN IE IC = - αN IE + I ;

Where, I is diode current.

IC = - αN IE + I0 (e Vc / VT – 1) I0 = - IC0 ; Where , I0 is the magnitude of reverse saturation current . . 3 . . IC = - αN IE – ICO (e VC / VT ) 3

subscript N to α indicates that we are using transistor in a normal manner.αI IC – IEO (e vE / VT – 1) 2 → Here. In such case current and junction voltage relationship for transistor is given by IE = . When we interchange the role of emitter and collector we operate transistor in a inverted function. αI is the inverted common – base current Gain. . subscript I to α indicates that we are using transistor in a inverted manner.Ebers moll model :- The Ebers-moll model for a PNP transistor → The general expression for collector current IC of a transistor for any voltage across collector junction Vc and emitter current IE is IC = -αN IN – ICO (e VC / VT – 1) 1 → Here. VE – The voltage drop from p – side to N – side at the emitter junction. IEO – The emitter junction reverse saturation current.

Therefore it is impossible to construct a transistor by simply connecting two separate diodes back to back. transistor action ceases. → Under there conditions.αI IC + I0 (e VE / VT – 1) IE = -αI IC – IE0 (e VE / VT – 1) → This model is valid for both forward & reverse static voltages applied across the transistor junction. →In the above model.αI IC + I IE = . and we simply have two diodes placed back. by making the base width much large than the diffusion length of minority carriers in the base. all mining carriers will recombine in the base and none will survive to reach the collector.Similarly applying KCL to emitter node we get IE + αI IC = I IE = I – αI IC = . .

Sign up to vote on this title
UsefulNot useful